Physiologic and Pathologic Angiogenesis - Signaling Mechanisms and Targeted Therapy 2017
DOI: 10.5772/67164
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Collateral Growth: Clinical Perspectives and Recent Insights

Abstract: This chapter summarizes recent research on the coronary collateral circulation. The chapter is focused on clinical perspectives and importance of a well-developed coronary collateral circulation, the mechanisms of growth induced by chemical factors and a role for stem cells in the process. Some discussion is devoted to the role of shear stress and mechanical signaling, but because this topic has been reviewed so extensively in the recent past, there is only small mention of its role in the growth of the corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…[43] Angiogenesis is the process of formation of capillaries as result of fluid shear stress which can only partly contribute to tissue perfusion, the conversion of these capillaries into functional collateral is termed as Arteriogenesis. [44] Bhamini Patel et al [45] suggested those collaterals can be formed without shear stress and ischemia can cause collateral growth which is mainly mediated by stem cells, chemical and genetic factors.…”
Section: Shear Stressmentioning
confidence: 99%
“…[43] Angiogenesis is the process of formation of capillaries as result of fluid shear stress which can only partly contribute to tissue perfusion, the conversion of these capillaries into functional collateral is termed as Arteriogenesis. [44] Bhamini Patel et al [45] suggested those collaterals can be formed without shear stress and ischemia can cause collateral growth which is mainly mediated by stem cells, chemical and genetic factors.…”
Section: Shear Stressmentioning
confidence: 99%
“…It is still not clear why some patients develop vigorous coronary collaterals and others do not. There are many papers dealing with the involved mechanisms, where stem cells also have an important role (6)(7)(8).…”
mentioning
confidence: 99%